2014
DOI: 10.1088/0004-6256/147/2/33
|View full text |Cite
|
Sign up to set email alerts
|

M Dwarf Catalog of the Lamost Pilot Survey

Abstract: We present a spectroscopic catalog of 58,360 M dwarfs from the Large Sky Area Multi-Object Fiber Spectroscopic Telescope pilot survey. For each spectrum in the catalog, spectral subtype, radial velocity, Hα equivalent width, a number of prominent molecular band indices, and the metal-sensitive parameter ζ are provided. We use the Sloan Digital Sky Survey Data Release 7 Spectroscopic M dwarf catalog to verify the precision of our methods of classifying the spectral types and measuring the radial velocities. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 47 publications
2
56
0
Order By: Relevance
“…Reiners et al (2012) showed that the fraction of active M stars (i.e., with H α detected in emission) increases from 5% for M0 to 55% for M4 dwarfs. Similar values for early and mid-type M dwarfs were obtained by Lépine et al (2013) and for the significantly more extended LAMOST survey analyzed by Yi et al (2014). This is less clear for later-type stars.…”
Section: Properties Of the M-dwarf Population In The Solar Neighborhoodsupporting
confidence: 82%
“…Reiners et al (2012) showed that the fraction of active M stars (i.e., with H α detected in emission) increases from 5% for M0 to 55% for M4 dwarfs. Similar values for early and mid-type M dwarfs were obtained by Lépine et al (2013) and for the significantly more extended LAMOST survey analyzed by Yi et al (2014). This is less clear for later-type stars.…”
Section: Properties Of the M-dwarf Population In The Solar Neighborhoodsupporting
confidence: 82%
“…(a) Some other publications and meta-archives that we have searched for potential CARMENES targets are Kirkpatrick et al (1991), Gizis (1997), Gizis & Reid (1997), Gizis et al (2000b), Henry et al (2002Henry et al ( , 2006, Mochnacki et al (2002), Gray et al (2003), Bochanski et al (2005), Crifo et al (2005), Lodieu et al (2005), Scholz et al (2005), Phan-Bao & Bessell (2006), Reylé et al (2006), Riaz et al (2006), Caballero (2007Caballero ( , 2009Caballero ( , 2012, Gatewood & Coban (2009), Shkolnik et al (2009, 2012, Bergfors et al (2010), Johnson et al (2010), Boyd et al (2011), Irwin et al (2011), West et al (2011, Avenhaus et al (2012), Deacon et al (2012), Janson et al (2012, 2014), Frith et al (2013, Jódar et al (2013), Malo et al (2013), Aberasturi et al (2014), Dieterich et al (2014), Riedel et al (2014), Yi et al (2014), , and the DwarfArchive at http://dwarfarchive.org. (b) PMSU: Reid et al (1995Reid et al ( , 2002; Hawley et al (1996); Gizis et al (2002).…”
Section: Carmenes Samplementioning
confidence: 99%
“…(a) Some other publications and meta-archives that we have searched for potential CARMENES targets are Kirkpatrick et al (1991), Gizis (1997), Gizis & Reid (1997), Gizis et al (2000b), Henry et al (2002Henry et al ( , 2006, Mochnacki et al (2002), Gray et al (2003), Bochanski et al (2005), Crifo et al (2005), Lodieu et al (2005), Scholz et al (2005), Phan-Bao & Bessell (2006), Reylé et al (2006), Riaz et al (2006), Caballero (2007Caballero ( , 2009Caballero ( , 2012, Gatewood & Coban (2009), Shkolnik et al (2009, 2012, Bergfors et al (2010), Johnson et al (2010), Boyd et al (2011), Irwin et al (2011), West et al (2011, Avenhaus et al (2012), Deacon et al (2012), Janson et al (2012, 2014), Frith et al (2013, Jódar et al (2013), Malo et al (2013), Aberasturi et al (2014), Dieterich et al (2014), Riedel et al (2014), Yi et al (2014), , and the DwarfArchive at http://dwarfarchive.org.…”
Section: Carmenes Samplementioning
confidence: 99%